A transcendental phenomenology on existential positive psychology (EPP) and L2 education: Setting a practical agenda for regulating students’ well-being and ill-being - Derakhshan , Ali; MacIntyre, Peter (Studies in Second Language Learning and Teaching, 2025)
The contributions of positive psychology (PP) to the study of second and foreign language (L2) emotions have received considerable scholarly attention in recent years. In response to the criticism that it adopted a limited viewpoint, PP has broadened its perspective. Existential positive psychology (EPP) is a branch of PP that can address prior critiques and inform English as a foreign language (EFL) learning, particularly the dialectical relationship between positive and negative emotions. Focus group interview data from eight experienced EFL teachers were analyzed to produce a five-dimensional model, including agendas and sample pedagogical practices. The five layers are “assigning meaningful, relevant, and authentic classroom tasks,” “providing personalized learning paths and plans for learners,” “empowering learner agency, choice, and responsibility,” “admitting and facing existential adversities/feelings,” and “cultivating a culture of positivity and appreciation.” The findings are discussed in light of PP and EPP, and implications are provided for EFL teachers, policymakers, and teacher educators to raise their awareness and knowledge of the EPP contribution to learner emotionality.